Standardization versus Adaptation Strategy in International Marketing Mix - The case of KFC in Vietnamese market - Bui, Mai (My University, 2020)
Nowadays in global business environment, it is essential for multinational companies to choose suita-ble marketing strategies in order to adjust to local characteristics of the foreign markets. The purpose of this study is to examine the choice of standardization and adaptation strategies in the marketing mix implemented by KFC fast food in Vietnamese market, it also integrates consumers’ perception towards the case company’s marketing mix implementation. The study focuses on investigating main elements of the marketing mix, they are product, price, place/distribution and promotion. Vietnamese market was selected thanks to its potentials for business expansion and its cultural differences in comparison with western markets. Additionally, KFC chain was chosen as an intensive case study since it was the first fast food brand to enter Vietnamese market and is now the leading brand in fast food segment, the brand is also well-recognized for its unique offerings based on local responsiveness in each oversea market. The theoretical framework of this thesis was constructed based on the literature of standardization and adaptation strategy, the marketing mix and the influences of culture on international marketing. In addition, the main sources of data were collected through secondary data, focus group interview, and the researcher’s own observation The research findings were in line with the theoretical framework by proving that the choice between standardization and adaptation is not a polarized one, marketers should find a mean to balance their global strategy and local adaptation in accordance with environ-mental factors, cultural differences and consumer behaviors across markets. Accordingly, KFC has made significant adjustment to each element of its marketing mix in Vietnamese market while main-taining its signature cooking methods and western dining customs. However, the main findings reveal that the degree of localization in KFC’s marketing mix has exceeded that of standardization due to the big differences in culture and consumers’ preference between the home market and the foreign mar-ket, especially in fast food sector. This research contributes some insights towards the discussion of standardization and adaptation strategies in cross-cultural setting. Also, the case of KFC fast food in Vietnam provides valuable sug-gestions for multinational companies to expand business and achieve their strategic plans in Vietnam-ese market
Keywords: Standardization, adaptation, marketing mix, KFC fast food, Vietnamese market